Global-scale performance of geothermal fields using power density and volumetric stored heat methods - Agno, Karen-Christian C. (Philippine Engineering Journal [eJournal])
The capacity of a geothermal power plant is generally based on the available geothermal resource. In this study, worldwide geothermal power production is examined in terms of installed capacity and total energy produced. Historical energy production data was used to assess the power density method and the stored heat method for resources estimation. The power density method was tested on 40 geothermal fields while for the stored heat method 14 geothermal power plants were considered to determine the 'actual' recovered energy that has been converted into useable electricity. All information used in this work used publicly available data. It was found that most geothermal fields have a power density of less than 10 MW/km2. It was observed a recovery factor of at least 11% was applicable in most fields with an average power output of at least 90 MW.